2017
DOI: 10.1111/ner.12642
|View full text |Cite
|
Sign up to set email alerts
|

Therapy-Related Explants After Spinal Cord Stimulation: Results of an International Retrospective Chart Review Study

Abstract: ObjectivesClinical trials of spinal cord stimulation (SCS) have largely focused on conversion from trial to permanent SCS and the first years after implant. This study evaluates the association of type of SCS and patient characteristics with longer‐term therapy‐related explants.Materials and MethodsImplanting centers in three European countries conducted a retrospective chart review of SCS systems implanted from 2010 to 2013. Ethics approval or waiver was obtained, and informed consent was not required. The ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 26 publications
(33 reference statements)
3
108
1
1
Order By: Relevance
“…Two studies have reported explant rates of 10 kHz SCS. The first study was a European multicenter, retrospective analysis that used data from 946 implanted subjects to derive annualized rates of explants defined as those that resulted in the termination of SCS therapy . The authors reported that the explant rate for inadequate pain relief was 5.0% per year of follow‐up for 10 kHz SCS, 5.5% for conventional rechargeable SCS, and 2.8% for nonrechargeable SCS.…”
Section: Explantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies have reported explant rates of 10 kHz SCS. The first study was a European multicenter, retrospective analysis that used data from 946 implanted subjects to derive annualized rates of explants defined as those that resulted in the termination of SCS therapy . The authors reported that the explant rate for inadequate pain relief was 5.0% per year of follow‐up for 10 kHz SCS, 5.5% for conventional rechargeable SCS, and 2.8% for nonrechargeable SCS.…”
Section: Explantsmentioning
confidence: 99%
“…The first study was a European multicenter, retrospective analysis that used data from 946 implanted subjects to derive annualized rates of explants defined as those that resulted in the termination of SCS therapy. 45 The authors reported that the explant rate for inadequate pain relief was 5.0% per year of follow-up for 10 kHz SCS, 5.5% for conventional rechargeable SCS, and 2.8% for nonrechargeable SCS. It is important to understand that 37.4% of the nonrechargeable devices were explanted and replaced due to battery depletion and , "real-world" analysis of satisfaction and explant rates in 10 kHz SCS commercial cases for any etiology.…”
Section: Explantsmentioning
confidence: 99%
“…The goal of neuromodulation therapy in the setting of chronic pain is to improve function and quality of life, decreasing the cost of the health care burden on society and reducing the opioid burden on the world population. Despite the successful use of SCS to treat many chronic pain syndromes, there are cases where SCS fails to produce initial or lasting relief . Dorsal root ganglion (DRG) stimulation is an option to improve outcomes in certain conditions that have challenged the efficacy of other forms of spinal stimulation and may, in fact, be the first choice of neuromodulation therapies for certain disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews of explant data also examined the potential reasons for device explantation. Pope and colleagues in their retrospective review of 352 SCS cases found that 43.9% (152/346) of explants occurred due to failure or lack of efficacy , and Van Buyten et al in a study of more than 900 patients, found that 50% of the devices were explanted due to therapeutic failure . These failures of device may suggest the need for different approaches, specifically with traditionally difficult pain patterns and regions.…”
Section: Introductionmentioning
confidence: 99%
“…Even in studies comparing battery life and explants, Drs. Sclafani and Leong states that HF10 therapy is commonly used for the most difficult LBP patients in Belgium 9 and HF10 was the lowest explant rate among rechargeable systems. This translates to a more convenient and comfortable experience and potentially less surgery for the patient with HF10.…”
Section: Case Scenariomentioning
confidence: 99%